The inter-war gold exchange standard credibility and monetary independence - Bordo, Michael D.; MacDonald, Ronald (NBER working paper series, 2001)
In this paper we analyze the operation of the inter-war gold exchange standard to see if the evident credibility of the system conferred on participating central banks the ability to pursue independent monetary policies. To answer this question we econometrically analyze two key parity, or arbitrage, conditions, namely uncovered interest rate parity and a yield gap relationship. We find that there were both long- and short-run deviations from the arbitrage conditions. The use to which this policy independence was put is analyzed in the context of a multivariate system, which includes reaction function variables.